Entamoeba histolytica Induce Signaling via Raf/MEK/ERK for Neutrophil Extracellular Trap (NET) Formation - Fonseca, Zayda (Front Cell Infect Microbiol, 2018)
Amoebiasis, the disease caused by Entamoeba histolytica is the third leading cause of human deaths among parasite infections. E. histolytica was reported associated with around 100 million cases of amoebic dysentery, colitis and amoebic liver abscess that lead to almost 50,000 fatalities worldwide in 2010. E. histolytica infection is associated with the induction of inflammation characterized by a large number of infiltrating neutrophils. These neutrophils have been implicated in defense against this parasite, by mechanisms not completely described. The neutrophil antimicrobial mechanisms include phagocytosis, degranulation, and formation of neutrophil extracellular traps (NETs). Recently, our group reported that NETs are also produced in response to E. histolytica trophozoites. But, the mechanism for NETs induction remains unknown. In this report we explored the possibility that E. histolytica leads to NETs formation via a signaling pathway similar to the pathways activated by PMA or the Fc receptor FcγRIIIb. Neutrophils were stimulated by E. histolytica trophozoites and the effect of various pharmacological inhibitors on amoeba-induced NETs formation was assessed. Selective inhibitors of Raf, MEK, and NF-κB prevented E. histolytica-induced NET formation. In contrast, inhibitors of PKC, TAK1, and NADPH-oxidase did not block E. histolytica-induced NETs formation. E. histolytica induced phosphorylation of ERK in a Raf and MEK dependent manner. These data show that E. histolytica activates a signaling pathway to induce NETs formation, that involves Raf/MEK/ERK, but it is independent of PKC, TAK1, and reactive oxygen species (ROS). Thus, amoebas activate neutrophils via a different pathway from the pathways activated by PMA or the IgG receptor FcγRIIIb.